PERLINDUNGAN HUKUM BAGI PEMBELI DALAM PERJANJIAN JUAL BELI HAND PHONE (HP) BEKAS DI KOTA PONTIANAK - NIM. A1011181118, AMOS HOTMA PANDAPOTAN SIMANJUNTAK (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT The implementation of legal protection in used mobile phone sales agreements has not been optimal due to ongoing issues experienced by buyers.The research question is: